TO THE PROBLEM OF PROFESSIONAL FORMATION COMPETENCIES OF FUTURE TEACHERS IN CONTEXTS OF THE BOLOGNA PROCESS - O.V. Mark (Academy of Cognitive and Natural Sciences, 2006)
This article considers the problem o f the formation of the professional competence o f a teacher in the context o f Boulogne process, the reasons o f modernization of Ukrainian higher education are analyzed.